2020
DOI: 10.1016/j.celrep.2020.108273
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Single-Cell Transcriptomics and Chromatin Accessibility Analysis Reveals Regulators of Mammary Epithelial Cell Identity

Abstract: Highlights d Generate combined scATAC-seq and scRNA-seq libraries of adult mouse MECs d Uncover luminal cell heterogeneity and molecular underpinning driving cell type/state d Identify the pre-committed lactation progenitor within the luminal progenitor compartment d Regulatory the grammar of MEC types and putative enhancer identification

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 40 publications
4
31
0
Order By: Relevance
“…Interesting, it was found that parity induced Aldh1a3 + luminal progenitor cells exist post involution, that were seemingly primed towards the alveolar lineage and expressed many lactation associated genes such as Lipa, Xdh and casein genes such as Csn2 and Csn3 [71] . Findings from a recent study that combined scATAC-Seq and scRNA-seq to study 10-week-old adult mice corroborated findings from the Bach study, identifying a single myoepithelial population as well as a Foxa1 + hormone responsive luminal population and Elf5 + /Kit + luminal cells (termed L -sec for luminal secretory, see Table 2 ) [83] . The L -sec cells were further divided into Rspo1 + /Aldh1a3 + luminal progenitor and Lalba + /Csn2 + /Lipa + lactation progenitor cells which according to pseudo temporal analysis suggests that the former gives rise to the latter cell subtype [83] .…”
Section: Using Single Cell Technologies To Understand Mammary Gland Biologysupporting
confidence: 54%
See 1 more Smart Citation
“…Interesting, it was found that parity induced Aldh1a3 + luminal progenitor cells exist post involution, that were seemingly primed towards the alveolar lineage and expressed many lactation associated genes such as Lipa, Xdh and casein genes such as Csn2 and Csn3 [71] . Findings from a recent study that combined scATAC-Seq and scRNA-seq to study 10-week-old adult mice corroborated findings from the Bach study, identifying a single myoepithelial population as well as a Foxa1 + hormone responsive luminal population and Elf5 + /Kit + luminal cells (termed L -sec for luminal secretory, see Table 2 ) [83] . The L -sec cells were further divided into Rspo1 + /Aldh1a3 + luminal progenitor and Lalba + /Csn2 + /Lipa + lactation progenitor cells which according to pseudo temporal analysis suggests that the former gives rise to the latter cell subtype [83] .…”
Section: Using Single Cell Technologies To Understand Mammary Gland Biologysupporting
confidence: 54%
“…Findings from a recent study that combined scATAC-Seq and scRNA-seq to study 10-week-old adult mice corroborated findings from the Bach study, identifying a single myoepithelial population as well as a Foxa1 + hormone responsive luminal population and Elf5 + /Kit + luminal cells (termed L -sec for luminal secretory, see Table 2 ) [83] . The L -sec cells were further divided into Rspo1 + /Aldh1a3 + luminal progenitor and Lalba + /Csn2 + /Lipa + lactation progenitor cells which according to pseudo temporal analysis suggests that the former gives rise to the latter cell subtype [83] . A limitation of this study was that analysis was only conducted at one time point, where comparisons between the gene expression profiles of the discovered lactation progenitor and previously described secretory alveolar cells [71] would have developmentally contextualised these findings.…”
Section: Using Single Cell Technologies To Understand Mammary Gland Biologysupporting
confidence: 54%
“…Interestingly, we identified distinguishable Egfr+Itga2+ and Kit+Itgb3+ positive subsets of Wfdc18+ cells, and also identified a Ly6a-subset of Esr1+ cells (Figure 6C,D). Although these cellular sub-states were not readily distinguishable in the non-imputed data, they may correspond to select cellular sub-states emerging from other recently published studies of cellular sub-types in the mammary gland (Regan and Smalley, 2020, Fu et al, 2020, Pervolarakis et al, 2020. Differential gene expression analysis between these subsets revealed the cells are likely distinguishable by broader transcriptomic differences representing distinct (although still quite similar) cell states (Figure 6D and Supplemental Table 2).…”
Section: Imputation Increases Detection Of Population Enriched Marker Genes and Identifies Cellular Subtypesmentioning
confidence: 73%
“…Recent advances in single cell technologies, such as single cell transcriptomics, have enabled a more detailed examination of mammary cell heterogeneity and, in the murine mammary gland, have enabled the reconstruction of developmental trajectories. A growing number of single-cell RNA sequencing (scRNA-seq) studies have analysed human 6,7 and mouse mammary epithelial cells (MECs) [8][9][10][11][12] and indicated the presence of three main epithelial cell types, namely basal/myoepithelial cells and two luminal subsets that closely corresponded to the EpCAM + /CD49f + and EpCAM + /CD49fpopulation designated as LP and LM cells in the human mammary gland. Importantly, additional heterogeneity within these main epithelial populations was described, albeit not consistently between these studies.…”
Section: Introductionmentioning
confidence: 99%